2016
DOI: 10.1136/bmjdrc-2015-000171
|View full text |Cite
|
Sign up to set email alerts
|

BeAM value: an indicator of the need to initiate and intensify prandial therapy in patients with type 2 diabetes mellitus receiving basal insulin

Abstract: IntroductionIn patients with type 2 diabetes mellitus (T2DM) with uncontrolled glycemia despite ongoing upward titration of basal insulin, targeting postprandial hyperglycemia may be required. Nevertheless, the point at which basal insulin is fully optimized and postprandial glucose (PPG) should be targeted with additional treatment remains unclear. We report here on the BeAM value (difference between bedtime and morning blood glucose values) as an indicator of the need to target PPG.MethodsThis study had 3 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 24 publications
3
27
0
15
Order By: Relevance
“…A proof‐of‐concept study, exploring the potential of the nocturnal glucose change measure, termed “BeAM”, as an indicator to intensify treatment targeting postprandial hyperglycaemia in people inadequately controlled on basal insulin, concluded that BeAM values between 2.5 and 3.1 mmol/L (45 and 55 mg/dL) should trigger the consideration of intensification . In our analysis, the median cut‐off was 3.1 mmol/L (56 mg/dL), which aligns with these observations, as only a modest improvement in HbA1c (−0.03%) was observed after 18 weeks' treatment with continued basal‐only treatment in participants with a nocturnal glucose change >3.1 mmol/L (56 mg/dL).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…A proof‐of‐concept study, exploring the potential of the nocturnal glucose change measure, termed “BeAM”, as an indicator to intensify treatment targeting postprandial hyperglycaemia in people inadequately controlled on basal insulin, concluded that BeAM values between 2.5 and 3.1 mmol/L (45 and 55 mg/dL) should trigger the consideration of intensification . In our analysis, the median cut‐off was 3.1 mmol/L (56 mg/dL), which aligns with these observations, as only a modest improvement in HbA1c (−0.03%) was observed after 18 weeks' treatment with continued basal‐only treatment in participants with a nocturnal glucose change >3.1 mmol/L (56 mg/dL).…”
Section: Discussionsupporting
confidence: 82%
“…In our analysis, the median cut‐off was 3.1 mmol/L (56 mg/dL), which aligns with these observations, as only a modest improvement in HbA1c (−0.03%) was observed after 18 weeks' treatment with continued basal‐only treatment in participants with a nocturnal glucose change >3.1 mmol/L (56 mg/dL). Further, they reported that large BeAM values may correlate with higher incidence of hypoglycaemia . Similarly, the incidence of hypoglycaemia was numerically higher in participants treated with basal‐only insulin, with a nocturnal glucose change >3.1 mmol/L (56 mg/dL) compared with those with nocturnal glucose change readings under this cut‐off; therefore, the use of the nocturnal glucose change as an indicator for intensification may also help prevent the unnecessary uptitration of basal insulin and the corresponding increase in the risk of hypoglycaemia with no additional benefit in glycaemic control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a recent pooled data analysis shows that prandial therapy should be considered when basal insulin doses are >0.5 IU/kg, although this should be assessed individually because some patients may be more insulin resistant than others . Another possible indicator of the need for starting prandial therapy is the appearance of large differences (>55 mg/dL [3.1 mmol/L]) between Bedtime and morning/AM (“BeAM” factor) blood glucose levels, large glucose drops overnight or between meals, an increase in the rate of nocturnal hypoglycemia, and an increase in the variability of FPG values …”
Section: Current Guidelines For Starting Prandial Therapymentioning
confidence: 99%